To simplify the expression \((15^6)^2\) using the power rule of exponents, we apply the rule which states that \((a^m)^n = a^{m \cdot n}\).
So, we have:
\[ (15^6)^2 = 15^{6 \cdot 2} = 15^{12} \]
Thus, \((15^6)^2\) is equivalent to \(15^{12}\).
15^3
15^4
15^8
15^12
1 answer
To simplify the expression \((15^6)^2\) using the power rule of exponents, we apply the rule which states that \((a^m)^n = a^{m \cdot n}\).
So, we have:
\[ (15^6)^2 = 15^{6 \cdot 2} = 15^{12} \]
Thus, \((15^6)^2\) is equivalent to \(15^{12}\).